Art in Architecture : Art for the Built Environment in the Province of Ontario - Parkin, Jeanne (Toronto : Visual Arts Ontario, 1982)
Allardyce, Anne ; Ariss, Margot ; Arn, Robert ; Astman, Barbara ; Bachinski, Walter ; Baird, Ron ; Balabanoff, Doreen ; Barry, Anne Meredith ; Bieler, Ted ; Blazeje, Zbignieuw ; Bloore, Ron ; etc.
Engels
boek
Keywords: Canada; Ontario